A Bismuth–Arene σ‐Complex – On the Edge of Menshutkin‐Type Complexes. Issue 9 (12th February 2019) - Bresien, Jonas; Schulz, Axel; Thomas, Max; Villinger, Alexander
Abstract : Mes*N(SiMe3 )BiCl2 (1, Mes* = 2, 4, 6‐tri‐ tert ‐butylphenyl) can be referred to as a hidden iminobismuthane, Mes*N=BiCl, which was thought to be generated in‐situ upon Me3 SiCl elimination triggered by a Lewis acid such as GaCl3 . Therefore, the reactivity of aminobismuthane1 was studied to find a synthesis route for the formation of a tetrazabismuthole in a [3+2] cycloaddition reaction with a covalently bound azide. However, reaction of1 with GaCl3 cleanly led to [Mes*N(SiMe3 )BiCl][GaCl4 ] (2 [GaCl4 ]), a compound with a Bi‐arene σ‐complex. Utilizing Ag[WCA] salts (WCA = weakly coordinating anion) for chloride abstraction, a C–C coupling product (3 ) was identified. The diiodide species Mes*N(SiMe3 )BiI2 (4 ) as precursor for a diazido species and the azido‐chloride compound Mes*N(SiMe3 )Bi(N3 )Cl (5 ) were also prepared to explore the possibility of a BiN4 heterocycle formation, again upon Me3 SiX elimination (X = halogen, N3 ), but4 and5 were unstable towards decomposition into a black precipitate and a complex product mixture. The structure and bonding of all isolated bismuth species is discussed. Abstract : Derivatives of the aminobismuthane Mes*N(SiMe3 )BiCl2 were synthesized. Chloride abstraction with GaCl3 led to the formation of a bismuth‐arene σ‐complex. The process is reversible in the presence of a Lewis base like Me3 SiN3 when the counter ion is [GaCl4 ] – . Abstracting a chloride anion by a silver salt containing a weakly coordinating anion led to C–C coupling products.